Study strategies used by medical students in the axis morphofunctional: A literature review (Research, Society and Development, 2021)
Objective: Identify in the main databases the study methods used by students during the learning process in the disciplines of the morphofunctional axis. Methodology: This is an Integrative Literature Review (RIL) in which, through a specific and rigorous literature search in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO), Educational Resources Information Center (ERIC) and PubMed. Results: 154 articles were found in the databases. 116 articles were selected in PubMed, 27 extracted from the ERIC platform, 9 articles in Scielo and 2 articles from LILACS. After applying the eligibility criteria, 12 articles were included in the RIL. Being articles from 11 different countries, all in the English language. Conclusion: The results presented demonstrate that the forms of learning of medical students contribute and evolve together with the course and are closely linked to the environment in which they are exposed, being fundamental in the search and fixation of knowledge.